Validation of Soil Test Based Fertilizer Prescription Model for Optimizing the Use of Chemical Fertilizer, Improved Performance of Brinjal (Solanum melongena L.) and Soil Biological Properties in Sub Tropical Mollisols. Issue 3 (4th February 2023) - Bhatt, Pallavi; Singh, Sobaran; Pant, Pawan Kumar
ABSTRACT: Incessant and disproportionate application of inorganic nutrients has deteriorated soil properties. An investigation was carried out to validate fertilizer requirement developed through soil test based crop response study to obtain desired yield of brinjal in Mollisol of Pantnagar during kharif season of 2019. The study revealed that maximum fruit yield, number of fruits per plants, fruit length and fruit diameter of brinjal was obtained under treatment with TY1 (250q ha −1 ) +10t ha −1 FYM (T6 ) (128:111:39 of N, P2 O5, and K2 O, respectively). In the initial phase of the investigation, experimental field was divided into three strip to which different doses of fertilizers were applied in low (no fertilizer application), medium (100:100:100 kg ha −1 of N, P, and K, respectively) and high (200:200:200 ha −1 of N, P, and K, respectively) proportion to create an artificial fertility gradient to bring heterogeneity in the experimental soil for the test crop. Further, in the second phase the response of brinjal to selected combinations through FYM, nitrogen, phosphorus and potassium in different soil fertility strips was also computed for spring and kharif seasons. With soil analysis, nutrient uptake studies, and yield the basic data for fertilizer prescription was worked out for both seasons. Further, using pooled data fertilizer prescription equation was generated for brinjal at different soil test values and yield targets. Response of brinjal in terms of growth, yield and nutrient uptake was studied to various soil test based fertilizer prescription at verification trial. The maximum microbial biomass carbon (427.29 μg g −1 soil), microbial biomass nitrogen (39.30 μg g −1 ), phosphates activity and dehydrogenase (150.36 µg TPF 24 h −1 g −1 soil) was reported under treatment TY2 (250q ha −1 ) +10t ha −1 FYM (T6 ) (128:111:39, of N, P2 O5 and K2 O, respectively). The balanced application of nutrients along with application of organic manure has ensured improvement in response of brinjal over general recommendation.